STRATEGI PEMBERANTASAN MAFIA TANAH MEWUJUDKAN KEPASTIAN HUKUM DAN KEADILAN AGRARIA DI KELURAHAN BANJAR AGUNG - Basyarudin, Basyarudin; Hasanudin, Tias Aprilia (BESIRU : Jurnal Pengabdian Masyarakat, 2025)
Land mafia practices pose a serious threat to legal certainty and agrarian justice in Indonesia, particularly in rural areas with low levels of legal literacy. This Community Service (PKM) activity was conducted in Banjaragung Village, Cipocok Jaya District, Serang City, as a strategic effort to prevent and eradicate land mafia through an educational and participatory approach. The methods used included land law counseling, mediation and paralegal training for community leaders, and the establishment of a Village Land Consultation Center (PKPD) as a local advocacy institution. The results of the activity demonstrated a significant increase in legal understanding among residents, the formation of a village paralegal network, and community commitment to supporting non-litigation land conflict resolution. This substantive justice-based approach and collective awareness have proven effective in strengthening land rights protection and building a robust legal defense system at the village level. This activity recommends replication of the PKPD model in other villages and the need for regulatory support from local governments for the sustainability of the community-based land mafia eradication program.